Selection and Clonal Propagation of High Artemisinin Genotypes of Artemisia annua - Wetzstein, Hazel Y.; Porter, Justin A.; Janick, Jules; Ferreira, Jorge F. S.; Mutui, Theophilus M. (Frontiers in Plant Science, 2018)
Artemisinin, produced in the glandular trichomes of Artemisia annua L. is a vital antimalarial drug effective against Plasmodium falciparum resistant to quinine-derived medicines. Although work has progressed on the semi-synthetic production of artemisinin, field production of A. annua remains the principal commercial source of the compound. Crop production of artemisia must be increased to meet the growing worldwide demand for artemisinin combination therapies (ACTs) to treat malaria. Grower artemisinin yields rely on plants generated from seeds from open-pollinated plants. Although selection has considerably increased plant artemisinin concentration in the past 15 years, seed-generated plants have highly variable artemisinin content that lowers artemisinin yield per hectare. Breeding efforts to produce improved F1 hybrids have been hampered by the inability to produce inbred lines due to self-incompatibility. An approach combining conventional hybridization and selection with clonal propagation of superior genotypes is proposed as a means to enhance crop yield and artemisinin production. Typical seed-propagated artemisia plants produce less than 1% (dry weight) artemisinin with crude yields below 25 kg/ha. Genotypes were identified producing high artemisinin levels of over 2% and possessing improved agronomic characteristics such as high leaf area and shoot biomass production. Field studies of clonally-propagated high-artemisinin plants verified enhanced plant uniformity and production of up to 70 kg/ha crude artemisinin. Tissue culture and cutting protocols for the mass clonal propagation of A. annua were developed for shoot regeneration, rooting, acclimatization, and field cultivation. Proof of concept studies showed that both tissue culture-regenerated plants and rooted cutting performed better than plants derived from seed in terms of uniformity, yield, and consistently high artemisinin content. Use of this technology to produce plants with homogeneously-high artemisinin can help farmers markedly increase the artemisinin yield per cultivated area. This would lead to increased profit to farmers and decreased prices of ACT.